The Chiastic Structure of Psalm 106 - Martin, Lee Roy (Old Testament essays, 2018)
This study describes the chiasm that is embedded within the narrative structure of Psalm 106. The author classifies the psalm as a historical recital of Israel's story, but within the psalm's narrative structure there is a chiasm that emphasizes key parallel elements. These elements draw the reader's attention to the themes of praise, prayer, salvation, rebellion and Moses, to name a few. Psalm 106 focuses on Israel's past failures and Yahweh's generous grace, motifs that highlight the need for repentance and forgiveness in any historical context, but especially in the exilic and postexilic periods.